COMPARISON BETWEEN MODIFIED OSWESTRY LOW BACK PAIN DISABILITY QUESTIONNAIRE AND ABERDEEN LOW BACK PAIN SCALE TAKING LOW BACK-SPECIFIC VERSION OF THE SF-36 PHYSICAL FUNCTIONING SCALE AS A GOLD STANDARD IN PATIENTS WITH LOW BACK PAIN - Lamba, Dheeraj; K Upadhyay, Ritambhara (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to compare the modified Oswestry low back pain (LBP) disability questionnaire with Aberdeen LBP scale (ABPS) and to find out which scale is better for functional assessment in LBP patients. Methods: A total of 100 randomly selected patients who fulfilled the inclusion criteria were recruited for the study. Modified Oswestry LBP disability questionnaire and ABPS were compared with a gold standard that is a low back-specific Version of the SF-36 Physical Functioning Scale. Statistical comparison was done using one-way ANOVA to find out which scale is better for assessing functional disability in LBP patients. Results: On analyzing the results using one-way ANOVA both the scales, i.e., modified Oswestry disability questionnaire and ABPS showed significant values indicating that both are equally reliable and effective tools and either can be used as outcome measurement tool in patients suffering from LBP. Conclusion: The present study concludes that the modified Oswestry disability questionnaire and Aberdeen low back scale both are equally reliable and effective outcome measurement tools for the assessment of patients suffering from LBP.